Generalized holographic complexity of rotating black holes - Ming Zhang; Jialong Sun; Robert B. Mann (Journal of High Energy Physics)
Abstract We explore the generalized holographic complexity of odd-dimensional Myers-Perry asymptotically Anti-de Sitter (MP-AdS) black holes with equal angular momenta within the “complexity equals anything” proposal. We begin by determining the codimension-one generalized volume complexity by finding the extremum of the generally covariant volume functional. Locally, we show that its late-time growth rate aligns with the critical momenta associated with the extremal hypersurfaces. Globally, we discover diverse phase transitions for the complexity at early times, including first-order, second-order, and multicritical transitions. An area law and a phase diagram are proposed to adapt to these phase behaviours, highlighting the effects of the black hole’s angular momentum. At zero time, we define the generalized holographic complexity of formation and examine its scaling relations for both large near-extremal MP-AdS black holes and static charged black holes. We find that the scaling behaviours of the generalized volume complexity of formation maintain uniformity with those of the original holographic complexity formulations, except in cases where the scalar functional defining the generalized holographic complexity is infinite in the vacuum limit or at spatial infinity. Additionally, we show that these findings can be applied to codimension-zero observables.